2007
DOI: 10.1073/pnas.0706011104
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Bacillus thuringiensis toxins by a fragment of a toxin-binding cadherin

Abstract: The insecticidal crystal proteins produced by Bacillus thuringiensis (Bt) are broadly used to control insect pests with agricultural importance. The cadherin Bt-R1 is a binding protein for Bt Cry1A toxins in midgut epithelia of tobacco hornworm (Manduca sexta). We previously identified the Bt-R1 region most proximal to the cell membrane (CR12-MPED) as the essential binding region required for Cry1Ab-mediated cytotoxicity. Here, we report that a peptide containing this region expressed in Escherichia coli funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
127
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(133 citation statements)
references
References 45 publications
(40 reference statements)
6
127
0
Order By: Relevance
“…In contrast, the comparable peptide, CR12-MPED from Bt-R 1 , gave a strong signal on dot blots and bound toxin at a high-affinity site (K d = 9 nM) and low-affinity sites (K d = 1 μM) (23). Although we were unable to quantify the dot blot binding data shown in Figure 7 and calculate the affinity value, qualitatively the data suggest that the affinity of Cry4Ba for the CR11-MPED peptide is much lower than the affinity of Cry1Ab for CR12-MPED from Bt-R 1 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, the comparable peptide, CR12-MPED from Bt-R 1 , gave a strong signal on dot blots and bound toxin at a high-affinity site (K d = 9 nM) and low-affinity sites (K d = 1 μM) (23). Although we were unable to quantify the dot blot binding data shown in Figure 7 and calculate the affinity value, qualitatively the data suggest that the affinity of Cry4Ba for the CR11-MPED peptide is much lower than the affinity of Cry1Ab for CR12-MPED from Bt-R 1 .…”
Section: Discussionmentioning
confidence: 99%
“…We (23) also reported that Cry1Ab binding to CR12-MPED was necessary for toxin enhancement properties. Based on the data in Chen et al (23) and evidence that Cry4Ba bound a C-terminal fragment of AgCad1 ( Figure 6, lanes 2 -8), we expressed the comparable CR11-MPED region from AgCad1 in E. coli and tested the purified 24 kDa peptide with Cry4Ba in bioassays of mosquito larvae. As shown in Figure 7, The CR11-MPED peptide increased the toxicity of Cry4Ba against A. gambiae fourth instar larvae.…”
Section: The Cr11-mped Region Of Agcad1 Enhances Cry4ba Toxicity To Amentioning
confidence: 99%
See 3 more Smart Citations